1996
DOI: 10.3146/i0095-3679-23-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Peanut Response to Prohexadione Calcium, a New Plant Growth Regulator

Abstract: Experiments in 1992Experiments in , 1993, and 1994 evaluated prohexadione calcium (calcium salt of 3,5-dioxo-4propionylcyclohexanecarboxylic acid) as a growth regu lator for peanut (Arachis hypogaea L.). Two experi ments in 1992 compared prohexadione calcium applied at 140 to 560 g ae/ha at the early pegging stage (PG) or at the row closure stage (RC). Greater suppression of main stem (MS) and cotyledonary lateral branch (CLB) length and greater row visibility at harvest were noted when prohexadione calcium w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(63 citation statements)
references
References 13 publications
(35 reference statements)
4
56
3
Order By: Relevance
“…Several plant growth regulators (PGRs) have been used for peanut (Wynne et al, 1974;Wu and Santelmann, 1977;Gardner, 1988;Mitchem et al, 1995;Mitchem et al, 1996;York et al, 1996). However, there are only a few reports that showed any increase of yield by the treatment with PGRs (Brown et al, 1973;Gorbet and Rhoads, 1975).…”
mentioning
confidence: 99%
“…Several plant growth regulators (PGRs) have been used for peanut (Wynne et al, 1974;Wu and Santelmann, 1977;Gardner, 1988;Mitchem et al, 1995;Mitchem et al, 1996;York et al, 1996). However, there are only a few reports that showed any increase of yield by the treatment with PGRs (Brown et al, 1973;Gorbet and Rhoads, 1975).…”
mentioning
confidence: 99%
“…Culpepper et al (1997) and Mitchem et al (1996) reported that prohexadione calcium improved row visibility of peanut and increased pod yield. Beam et al (2002) reported that increased pod yield of peanut by prohexadione calcium was attributed in part to increased pod retention and less pod loss during digging and inversion of vines.…”
mentioning
confidence: 99%
“…Pro-Ca has been registered in the U.S.A and Europe for use on apple [65], rice [63], petunia and okra plants [66], Camarosa strawberry [67], sorghum [68] and peanut [69]. Application of Pro-Ca reduces the length of stem internode and vegetative growth of fruit trees including apple [70], pear [62] and cherry [71].…”
Section: Dwarfing By Chemical Treatmentmentioning
confidence: 99%
“…The compound has been reported to have no negative effect on yield, fruit quality, fruit set and flower initiation [62,70,72], although delayed initiation of flowering or fruit set has been reported in several studies [66]. Pro-Ca significantly shortened the annual shoots of a walnut cultivar [73], and greatly suppressed the stem length of peanut [69] and sweet sorghum crops [74]. Pro-Ca does not persist in the plant therefore does not directly affect vegetative growth in the following season [63].…”
Section: Dwarfing By Chemical Treatmentmentioning
confidence: 99%